Sustaining Himalayan agriculture under changing climate scenario - Lama, Yangdup; Agarwal, Rishu; Singh, Shishir Kumar; Arunachalam, Ayyanadar (Annals of Agricultural Research, 2017)
The biodiversity rich Indian Himalayan Region (IHR) harbours diverse culture in the lifestyle ofpeople residing therein who have adapted to the geographic toughness and climate uncertaintiesover a period of time. Sustaining these humans with food and nutrition calls for focussedunderstanding of food production systems in the ecologically fragile environment. Further, thegrowing impact of climate change is marginalizing life of people despite abundance of naturalresources. The paper focuses on the ecological characteristics, socio and cultural aspects andchallenges of agriculture in three physiographic divisions of IHR viz., north-western Himalaya,central Himalayan and the north-eastern Himalayan region. Initiatives to promote climate resilientagriculture for sustaining the Himalayan agriculture have also been discussed in this paper.